The perennial matchmaker : create amazing combinations with your favorite perennials - Ondra, Nancy J. (Rodale, 2016)
Want foolproof ideas for pairing favorite perennials with an array of harmonious plant partners but don't know where to start? Plantswoman Nancy J. Ondra helps you to jump-start your perennial garden with her one-plant-at-a-time approach for choosing plant partners. Having spent more than 30 years growing and experimenting with perennials and plant combinations, Ondra shares her extensive experience in this in-depth guide to eye-catching color combinations, dramatic textural displays, and stunning seasonal effects. The Perennial Matchmaker features 80 individual perennial profiles, close to 400 exquisite photographs of plant partnerships, and Ondra's insight into the wide array of plants that make great combinations, including annuals, bulbs, grasses, shrubs, and other perennials. Each plant profile gives dozens of ideas and suggestions for pairings, including region-specific choices, Ondra's top-choice perfect match, and an at-a-glance summary of the best color partners.